Development of E-Module on Economic Education Management as a Learning Alternative Using Learning Management System (LMS) during the Covid-19 Pandemic - Mispandi; Muh Fahrurrozi (Edunusa: Journal of Economics and Business Education, 2022)
This research aims to; 1) develop an E-module on the management of economic education as an alternative to learning economics education using a learning management system during the covid 19 pandemic, and 2) know the feasibility of developing an E-Module for managing Economics education according to material and media design experts and student responses. This research is a type of R & D development research (Research and Development) because it seeks to develop an E-Modul using the ADDIE development model. The subjects of this study were 2 material experts, 2 media, experts, and 62 economic education students. The data collection techniques used in this study used three kinds of techniques, namely: observation, interviews, and, questionnaires. The data analysis technique used in this study is a quantitative descriptive analysis technique. The results of the research and development of the economic education management e-module can be concluded that the feasibility of the economic education management e-module product as seen by the material experts obtained an average score of 3.57 which is included in the very feasible category. And the feasibility of the e-module product on the management of economic education seen by media experts obtained an average score, of 3.60 which was included in the very feasible category. As well as student responses obtained an average overall score of 3.38 which is classified as a very feasible category